Evaluating the Protestant Community's Action Towards Democratization During the Period of Martial Law in Taiwan - Syvrais-Gallant, Alexandre (Université d'Ottawa / University of Ottawa, 2015)
This thesis examines the reasons why certain Protestant churches in Taiwan during the martial law period advocated democratization, while others did not. It uses an institutional and organizational theory to better understand the inner workings of these churches to understand their norms and values in terms of their overall group culture. This is set against previous English-language research that focused primarily on the ideals of essentialized or reified religions, broadly defined, without looking at the variations that exist between different churches. It argues that in order to understand the actions of these churches towards democratization, we must look at the whole of each organization. The norms and values, on their own, are insufficient to explain their motivations.
Keywords: Taiwan; China; Religion; Christianity; Democracy; Democratization; Martial Law; Protestantism; Presbyterians; Baptists; Local Church